Association of Mycoplasma ovipneumoniae Infection with Respiratory Disease in Swedish Sheep - Asp Tauni, Felicia (2012)
SUMMARY The Swedish lamb production is steadily increasing and pneumonia is one of the diseases causing the greatest income losses. Pneumonia and pleuritis are two of the most common post-mortem inspection findings registered at routine slaughter amongst both sheep and lambs, and pneumonia is the most common finding at necropsied adult sheep that have been found dead. It is essential to know which infectious agent causing the pneumonia in order to design an ideal treatment protocol for the flock. But the diagnostics of live animals is problematic and limited both by cost and by the fact that several of the bacteria is part of the commensal flora of the upper respiratory tract of healthy sheep, which can make the results unreliable. Mycoplasma ovipneumoniae is one of the agents associated with respiratory disease and is a part of the aetiology of mycoplasmosis, also called atypical pneumonia. Penicillin is generally the first choice of treatment of suspected pneumonia but Mycoplasma spp. are naturally resistant against penicillin and therefore require antibiotics with a broader spectrum whether it should be treated. To reduce unnecessary use of broad-spectrum antibiotics it is necessary to increase knowledge about pneumonia in sheep and to develop the diagnostics. If there were a way to determine the cause of the lesions already at the post-mortem inspection at slaughter you could get a foundation for a treatment strategy. Therefore, the aim of this study has been to examine whether a specific agent can be correlated to a specific gross pathological or histopathological appearance, as well as studying the prevalence of Mycoplasma ovipneumoniae and other bacterial agents in lung lesions found at routine slaughter in Sweden. A total of 44 lungs with pneumonic lesions were collected from two slaughterhouses during the period of September-October. The lungs were examined macroscopically and histologically, photographed and samples were taken for a microbiological investigation including an aerobic bacterial culture and a Mycoplasma PCR. Three of the lungs were excluded from the project due to a deviant gross or histological appearance. Mycoplasma ovipneumoniae were isolated in 76% of the remaining lungs and Mannheimia haemolytica in 63%, always in combination with Mycoplasma spp. Mycoplasma ovipneumoniae did not correlate with any of the histological findings but could be correlated to a specific gross appearance. The study is financed by the Swedish SvarmPat program.